EFEKTIVITAS PEMASARAN KARANG HIAS PADA PT. AGUNG AQUATIC MARINE, BALI DENPASAR - Elisabeth Pandang; I Made Tamba; Ni Putu Anglila Amaral (Berajah Journal, 2026)
Marketing effectiveness is an important factor in supporting the success of a company, particularly in the ornamental coral business which has sensitive product characteristics, high economic value, and export orientation. This study aims to analyze the marketing effectiveness of ornamental coral based on the marketing mix approach (4Ps), consisting of product, price, place, and promotion, as well as to identify internal and external supporting and inhibiting factors at PT. Agung Aquatic Marine Bali. This research employed a descriptive quantitative method. Data were collected through questionnaires, interviews, and observations involving 15 respondents consisting of management and employees directly engaged in marketing activities. The data were analyzed using a Likert scale to measure the level of effectiveness in each aspect of the marketing mix examined in this study. The results indicate that the overall marketing effectiveness of ornamental coral is categorized as effective to very effective. The product and promotion aspects achieved the highest effectiveness levels due to export-quality products and strong communication with international buyers. Meanwhile, the price and distribution aspects were categorized as effective, although several constraints were identified, including fluctuating market demand and strict export regulations.Based on these findings, the company is expected to maintain its product quality and promotional strategies while improving pricing optimization and market diversification in order to enhance sustainable competitiveness in the global market.